Intertext – paratext – translation: Boris Akunin's extracurricular reading in Russian and Polish - Kaźmierczak, Marta (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2016)
The paper discusses a peculiar way of dialoguing with tradition, namely by way of intertitles, as is the case in Boris Akunin’s novel Vneklassnoye chtenie (Extracurricular Reading). The effectiveness of the dialogue is also measured in intercultural perspective, based on the Polish translation by Ewa Rojewska-Olejarczuk.